Level of Birth Preparedness and Complication Readiness among Pregnant Women Residing In Urban Slums of Shivamogga City, India - Avinash A Patil; Raghavendraswamy Koppad; Kanchana Nagendra; Chandrashekar SV (Medsci Publications, 2022)
Background: Safe motherhood is about informing and educating woman about danger signs in pregnancy, how to identify and seek advice from health personnel and prepare for safe confinement. In public health system, in India it is the responsibility of ASHA to motivate the pregnant woman in her area for safe institutional delivery. BPACR is a tool which assesses, how well the pregnant women are prepared for the challenges in pregnancy. Aim& Objective: To ascertain the level of awareness of Birth Preparedness and Complication Readiness (BPACR) among antenatal mothers residing in urban slums . Methodology: A community based cross-sectional study was conducted among pregnant women residing in urban slums of Shivamogga, Karnataka. Data was collected using pre-designed questionnaire, "Monitoring BP/CR‑tools and indicators for maternal and new born health" of the "JHPIEGO". Data was analysed and results were tabulated. Results: In this study, only 42% of pregnant women knew about the term 'Birth preparedness' while the rest 58% pregnant women did not know it. Education status and complication experienced during present or previous pregnancy were found to have significant association with BPACR. Identification of blood donor and skilled birth provider were less among study group. Conclusions: Awareness of danger signs and complication readiness was found to be good in our study.